2011
DOI: 10.1111/j.1538-7836.2011.04450.x
|View full text |Cite
|
Sign up to set email alerts
|

Aspirin has little additional anti‐platelet effect in healthy volunteers receiving prasugrel

Abstract: SummaryBackground: Strong P2Y12 blockade, as can be achieved with novel anti-platelet agents such as prasugrel, has been shown in vitro to inhibit both ADP and thromboxane A2-mediated pathways of platelet aggregation, calling into question the need for the concomitant use of aspirin. Objective: The present study investigated the hypothesis that aspirin provides little additional anti-aggregatory effect in a group of healthy volunteers taking prasugrel. Study participants/methods: In all, 9 males, aged 18 to 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 32 publications
4
15
0
Order By: Relevance
“…By far the most common abnormalities were reduced platelet function with the ASPI‐test and adrenaline reagents. Since both reagents are sensitive to dysfunction of the platelet cyclooxygenase pathway28, 40, this finding is consistent with the high proportion of patients receiving aspirin (approximately 75%). Reduced platelet function with the ADP‐test was less common, reflecting the lower number of patients with any exposure to P2Y 12 blockers before surgery (approximately 20%) 28…”
Section: Discussionsupporting
confidence: 72%
“…By far the most common abnormalities were reduced platelet function with the ASPI‐test and adrenaline reagents. Since both reagents are sensitive to dysfunction of the platelet cyclooxygenase pathway28, 40, this finding is consistent with the high proportion of patients receiving aspirin (approximately 75%). Reduced platelet function with the ADP‐test was less common, reflecting the lower number of patients with any exposure to P2Y 12 blockers before surgery (approximately 20%) 28…”
Section: Discussionsupporting
confidence: 72%
“…Most groups have studied aggregation in response to ADP, collagen and thrombin receptor-activating peptide (TRAP)-6 (or thrombin in washed platelets), while others have also investigated the effects of epinephrine, serotonin, the thromboxane (Tx) A 2 mimetic U46619, and ristocetin (1013). There is little consensus from these various groups with regard to the specific concentrations of agonists to be used.…”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…The majority of this work concerns the characterization of platelet reactivity in the presence of antiplatelet therapies such as GPIIb/IIIa inhibitors (16,23) or dual anti-platelet therapy with ADP P2Y 12 antagonists plus aspirin (1013,17,21,22,25,26). Using these techniques, it is possible to produce concentration-response curves which can be used to evaluate the pharmacological action of these therapies.…”
Section: -Well Plate Aggregationmentioning
confidence: 99%
“…These agents have also been shown to block thromboxane-mediated pathways, which calls into question whether aspirin is even needed in conjunction with these antiplatelets [54]. Several pharmacodynamics studies have shown that aspirin provides little additional antiplatelet effect when used with potent P2Y 12 Optimal aspirin dose in acute coronary syndromes: an emerging consensus REviEW future science group www.futuremedicine.com inhibitors [55][56][57]. At this time, no clinical trial has tested the impact of aspirin in the presence of strong P2Y 12 receptor blockade.…”
Section: Newer P2y 12 Receptor Antagonists (Prasugrel and Ticagrelor)mentioning
confidence: 97%